Leveraging Social Media Platforms for valuing Agri-Entrepreneurship in Punjab, India - Amanjit Kaur,; Gurjeet Singh Walia, Ramandeep Singh, (Indian Journal of Extension Education, 2022)
Social media tools offer a huge opportunity to value digital engagement for agribusiness stakeholders. The rapid pace of developing digital platforms calls for substantial growth in agri-entrepreneurship in Punjab. The present study analyzed the usage pattern of different social media platforms by agripreneurs in Punjab and examined the significance of their demographic characteristics in the usage of these online communication platforms. The data were collected from 200 agripreneurs, who got or were getting training from Punjab Agricultural University during the year 2019. The findings highlighted that WhatsApp and Facebook were the two topmost used social media applications for agribusiness pursuits in Punjab, followed by Instagram, YouTube, Twitter, and LinkedIn. Among various demographic attributes, age, educational qualification, and marital status of the agripreneurs were found to have significant relationships with their usability in agribusiness. The young, highly educated, and unmarried agripreneurs recorded more use of social media tools for agribusiness undertakings as compared with older, less educated, and married agripreneurs. It can be concluded that all agribusiness stakeholders should encourage the synchronized use of such digital platforms to make the right information available at right time to the agripreneurs